Code‐Switching to Navigate Social Class in Higher Education and Student Affairs. Issue 162 (13th June 2018) - Elkins, Becki; Hanke, Eran
Abstract: This chapter outlines the concepts of social class privilege, highlights the experiences of students navigating social class, and examines the role of code‐switching as a strategy to navigate higher education.